Gastrointestinal Complaints and Treatment of Helicobacter pylori in Children: A Narrative Review - Mohammad Sobhani Shahmirzadi; Fatemeh Ghasemi-Kebria; Gholamreza Roshandel (Mazandaran University of Medical Sciences, 2016)
Context: The role of Helicobacter pylori infection in children's problems is considered in recent years. Helicobacter pylori, a gram negative spiral flagellate organism has diverse effects and consequences on children's health, but in some issues especially in chronic abdominal pain its role continues to debate. The prevalence of H. pylori infection and remedial measures against it in Iranian children is increasing. Evidence Acquisition: Diagnostic tests are divided into two categories: Invasive and noninvasive. Diagnostic methods are available and although invasive methods are more accurate and reliable; non-invasive methods are more acceptable and practical for children. Serological diagnosis assays are not worth much in the pediatric fields. Results: It is important to emphasize that diagnostic methods for H. pylori are revised and in some conditions, such as chronic abdominal pain, contrary to the impression, no treatment is required. Conclusions: Triple therapy is a reasonable method to eradicate H. pylori in the first stage, but different combinations and one week courses in the Iranian studies were successful.